Students’ Experiences on Implementation of Augmented Reality Material in Islamic Boarding School to Improve Students’ Vocabulary - Fitrah Amalia Sofyan; Masruddin; Sukirman (Universitas Islam Negeri Palopo, 2026)
This study aims to investigate the use of Augmented Reality (AR) in enhancing English vocabulary learning among students in an Islamic boarding school (pesantren) context. The research was conducted at Islamic boarding school on Palopo using a qualitative case study approach. The participants consisted of six female students aged 12–17 who were selected based on their active participation in English learning activities. The study utilized Octagon Company AR flashcards as the primary learning media. Data were collected through classroom observations and semi-structured interviews and were analyzed using thematic analysis. The findings reveal three main themes: (1) enhanced vocabulary retention, (2) increased learning motivation, and (3) implementation challenges in the pesantren environment. The use of AR significantly improved students’ vocabulary acquisition, as indicated by an average assessment score of 81.93, and increased their engagement through interactive and visual learning experiences. However, challenges such as limited access to devices, internet restrictions, and institutional rules in pesantren were identified as barriers to implementation. This study suggests that AR has strong potential as an innovative tool for English language learning in traditional educational settings. It is recommended that pesantren administrators and educators consider integrating AR-based learning with appropriate technological support and policy adjustments to maximize its effectiveness while maintaining institutional values.